Preparation method and application of CuFe-SAPO-34 molecular sieve nanosheet assembly

By synthesizing CuFe-SAPO-34 molecular sieve nanosheet assembly using natural kaolin and natural copper ore, the problem of insufficient stability and sulfur resistance of Cu-SAPO-34 catalyst under low temperature hydrothermal conditions was solved, and excellent NH3- SCR catalytic activity and low temperature water and sulfur resistance.

CN116351465BActive Publication Date: 2025-02-14FUZHOU UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310324975.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-30
Publication Date
2025-02-14
Estimated Expiration
2043-03-30

AI Technical Summary

Technical Problem

The Cu-SAPO-34 catalyst has poor stability under low temperature hydrothermal conditions and insufficient sulfur resistance, which limits its application in NOx selective catalytic reduction reaction.

Method used

Natural kaolin and natural copper ore are used as all copper and iron sources, and CuFe-SAPO-34 molecular sieve nanosheet assembly is obtained by high-temperature roasting and dry adhesive method to regulate the distribution form of Fe and Cu species to achieve high dispersion.

Benefits of technology

Improve the low-temperature water and sulfur resistance of CuFe-SAPO-34 molecular sieve, significantly improves its catalytic activity and stability in NH3-SCR reaction, and can maintain a NOx conversion rate of more than 90% under 80,000h-1 spacespeed conditions. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116351465B_ABST
    Figure CN116351465B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of a CuFe-SAPO-34 molecular sieve nanosheet assembly. The preparation method is to fully mix natural kaolin and natural copper ore to obtain a mineral mixture, then subject the mixture to high-temperature roasting treatment, and use the roasted mineral mixture as all silicon sources, iron sources and copper sources, and obtain the CuFe-SAPO-34 molecular sieve by one-step synthesis through a dry gel method. The present invention can regulate the depolymerization state of kaolin by changing the roasting temperature to change the thickness of the SAPO-34 molecular sieve nanosheet, and can achieve a high degree of dispersion of Cu and Fe species in the SAPO-34 molecular sieve by regulating the occurrence form of Fe and Cu species in the mineral mixture, thereby preparing a CuFe-SAPO-34 denitration catalyst with excellent catalytic activity and low-temperature water and sulfur resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of environmentally friendly catalysts, and specifically relates to a method for preparing a CuFe-SAPO-34 molecular sieve nanosheet assembly and its application in NO x Application in selective catalytic reduction reactions. Background Art

[0002] Nitrogen oxides (NO x ) emissions pose a serious threat to air pollution and human health. How to deal with NO x Pollutants have received close attention from the public. Ammonia selective catalytic reduction (NH3-SCR) denitrification technology is considered to be one of the most promising denitrification technologies. Copper-based molecular sieve catalysts are considered to be the most promising catalysts in NH3-SCR reactions. In recent years, small-pore Cu-SAPO-34 molecular sieves have received widespread attention due to their unique pore structure, wide active temperature window, and good high-temperature hydrothermal stability. However, at present, the Cu-SAPO-34 catalyst still has the following two problems: ① Poor low-temperature hydrothermal stability. Cu-SAPO-34 is prone to skeleton collapse and agglomeration of active Cu species under low-temperature hydrothermal conditions; ② Poor sulfur resistance. SO2 in the tail gas is easy to generate (NH4)2SO4 during the reaction process, which blocks the molecular sieve pores and covers the active center. Therefore, the application of Cu-SAPO-34 catalyst in the field of denitrification is severely limited.

[0003] Studies have shown that the high external specific surface area of ​​nano / hierarchical pore molecular sieves is beneficial to improving the dispersion of active Cu species and inhibiting the formation of CuO during hydrothermal aging. x The generation of species, and the shorter diffusion path can increase the mass transfer rate, allowing (NH4)2SO4 to diffuse quickly out of the molecular sieve, thereby improving the water and sulfur resistance of the catalyst. In addition, the introduction of a second metal such as Fe, Ce, etc. is also an effective measure to improve the denitrification performance and water and sulfur resistance of the catalyst. The second metal not only helps to improve the dispersion of active Cu species, but also serves as a second active site to synergistically promote catalytic performance.

[0004] The open literature (ChemCatChem, 2019, 11(16): 3865-3870) studied the effect of grain size on the NH3-SCR performance of Cu / S APO-34 catalyst and found that the nano Cu / SAPO-34 catalyst is beneficial to the dispersion of active Cu species and inhibits the formation of CuO. x agglomeration, thereby improving its catalytic activity in NH3-SCR; at the same time, due to the presence of more isolated Cu 2+ ions, nanocatalysts exhibited better resistance to hydrothermal aging.

[0005] Public literature (ChemCatChem, 2020, 12(19): 4871-4878) synthesized a hierarchical pore Cu / SAPO-34 catalyst using CaCO3 as a hard template. The hierarchical pore structure can increase the external specific surface area, accelerate the mass transfer rate, and help promote the generation and dispersion of active copper species, thereby making the catalyst exhibit better water and sulfur resistance.

[0006] The open literature (Catalysis Communications, 2016, 81: 20-23) introduced Ce into Cu-SAPO-34 and found that the addition of Ce can not only improve the active Cu 2+ It can not only reduce the content and inhibit the formation of CuO, but also stabilize the molecular sieve framework structure, thereby improving the NH3-SCR activity and low-temperature water resistance.

[0007] The open literature (Catalysts, 2020, 10(3): 321-341) prepared Cu / SAPO-34, Fe / SAPO-34 and Cu-Fe / SAPO-34 molecular sieves by ion exchange method. The Cu-Fe / SAPO-34 catalyst showed higher NO x conversion and low-temperature water resistance, which is due to the synergistic effect between iron and copper, which makes the catalyst more active Cu 2+ and Fe 3+ Species.

[0008] Patent CN107126973A discloses an in-situ synthesis method of a CuFe-SAPO-34 catalyst and its application. The method controls the Fe loading in the molecular sieve by changing the amount of Fe salt input. The CuFe-SAPO-34 catalyst with the optimal Fe loading exhibits significantly improved high-temperature denitrification activity and low-temperature water resistance.

[0009] At present, although there are many preparation methods dedicated to improving the low-temperature water and sulfur resistance of Cu-SAPO-34 molecular sieves, there is no method for in-situ preparation of Cu Fe-SAPO-34 molecular sieve nanosheet assemblies using natural kaolin and natural copper ore as all copper and iron sources. Summary of the invention

[0010] In order to improve the low-temperature water and sulfur resistance of Cu-SAPO-34 molecular sieve, the present invention provides a green preparation method and application of a CuFe-SAPO-34 molecular sieve nanosheet assembly.

[0011] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: natural kaolin and natural copper ore are mixed evenly to obtain a mineral mixture, and then the mineral mixture is subjected to high-temperature calcination treatment, and the calcined mineral mixture is used as all silicon sources, iron sources and copper sources, and the CuFe-SAPO-34 molecular sieve is synthesized in one step by a dry gel method.

[0012] Specifically, a method for preparing a CuFe-SAPO-34 molecular sieve nanosheet assembly comprises the following steps:

[0013] (1) placing natural kaolin and natural copper ore in a high-speed pulverizer and fully pulverizing and mixing them to obtain a mineral mixture;

[0014] (2) placing the mineral mixture in a muffle furnace for high-temperature roasting;

[0015] (3) mixing the calcined mineral mixture with phosphoric acid and reacting them sufficiently to obtain an activated mineral mixture;

[0016] (4) mixing the activated mineral mixture with a supplemental aluminum source and phosphoric acid, stirring thoroughly, and then drying in an oven to obtain a xerogel;

[0017] (5) The dry gel is placed in a built-in weighing bottle of a reactor, deionized water and a microporous template are added to the bottom of the reactor, the reactor is sealed and transferred to an oven for crystallization. After the crystallization is completed, the product is cooled, centrifuged, dried, and calcined to obtain a CuFe-SAPO-34 molecular sieve nanosheet assembly.

[0018] Furthermore, in step (1), the sum of the content of silicon dioxide and aluminum oxide in the natural kaolin is not less than 85wt%, and the content of iron oxide is not less than 3wt%; the natural copper ore is one or a mixture of chalcocite, cuprite, chalcopyrite, hydrochalcopyrite and chalcopyrite; the mass ratio of the natural kaolin to the natural copper ore is 1 to 5:1; the rotation speed of the high-speed pulverizer is 5000 to 40000 r / min, and the pulverization time is 5 to 60 min.

[0019] Furthermore, the calcination temperature in step (2) is 300-1000° C., and the calcination time is 1-14 hours.

[0020] Furthermore, the phosphoric acid concentration in step (3) is 5 to 14 mol / L; the mass ratio of the activated mineral mixture to phosphoric acid is 1:2 to 11, the reaction temperature is 30 to 100° C., and the reaction time is 1 to 24 h.

[0021] Furthermore, in step (4), the amounts of the activated mineral mixture, the supplementary aluminum source, and the phosphoric acid meet the following conditions: the molar ratio of P2O5 / Al2O3 is 0.7-1.2, the molar ratio of SiO2 / Al2O3 is 0.2-0.8, and the molar ratio of Cu / Al2O3 is 0.06-0.36; the supplementary aluminum source is a mixture of one or more of pseudo-boehmite, aluminum isopropoxide, and sodium aluminate, the drying temperature is 30-100°C, and the drying time is 6-48h.

[0022] Furthermore, in step (5), the molar ratio of H2O added to the bottom of the kettle to Al2O3 in the dry gel is 30-100, and the molar ratio of the microporous template to Al2O3 in the dry gel is 1.8-3.4; the microporous template includes one or a mixture of triethylamine, tetraethylammonium hydroxide, diisopropanolamine, n-butylamine, tetraethylenepentamine, and N,N-diisopropylethylamine; the crystallization temperature is 170-220°C, the crystallization time is 24-96h, the calcination temperature is 400-800°C, and the calcination time is 2-8h.

[0023] Furthermore, the copper loading of the CuFe-SAPO-34 molecular sieve nanosheet assembly is 0.5-9wt%, and the iron loading is 0.5-4wt%; the molecular sieve morphology is a cubic and spherical structure self-assembled by nanosheets, the sheet thickness is 2-150nm, and the grain size is 3-50μm.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The CuFe-SAPO-34 molecular sieve nanosheet assembly synthesized by the present invention uses natural mineral kaolin and natural copper ore as all copper and iron sources, and directly introduces Cu and Fe elements into the SAPO-34 molecular sieve. This method has the advantages of simple operation and low cost.

[0026] 2. The CuFe-SAPO-34 molecular sieve synthesized in the present invention has a cubic morphology formed by self-assembled nanosheets. The depolymerization state of kaolin can be regulated by changing the calcination temperature to change the thickness of the SAPO-34 molecular sieve nanosheets. The occurrence form of Fe and Cu species in the composite can be regulated by changing the mixing ratio of kaolin and natural copper ore and the calcination temperature to achieve high dispersion of Cu and Fe species in the SAPO-34 molecular sieve.

[0027] 3. The nanosheet morphology of the CuFe-SAPO-34 molecular sieve synthesized in the present invention can promote the high dispersion of Cu and Fe species in the SAPO-34 molecular sieve, effectively solve the problem of low-temperature diffusion limitation, reduce the generation of ammonium sulfate, and thus show excellent SCR catalytic activity and low-temperature water and sulfur resistance. Therefore, the CuFe-SAPO-34 molecular sieve can be used as NOx Catalyst for selective catalytic reduction reaction. -1 Under the condition of space velocity, the denitrification efficiency of fresh CuFe-SAPO-34 molecular sieve catalyst in the range of 175-550℃ can reach more than 90%; after low-temperature hydrothermal aging treatment, it still has a wide active temperature window (200-475℃); at 200℃, 200ppm SO2 and 10% H2O are introduced for 6 hours of continuous reaction, and the NO x The removal rate can still be maintained above 90%. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The X-ray diffraction (XRD) pattern of the CuFe-SAPO-34-1 molecular sieve obtained in Example 1;

[0029] Figure 2 This is a scanning electron microscope (SEM) image of the CuFe-SAPO-34-1 molecular sieve obtained in Example 1;

[0030] Figure 3 The denitration performance diagram of the fresh sample and the low-temperature hydrothermal aged sample of CuFe-SAPO-34-1 molecular sieve obtained in Example 1;

[0031] Figure 4 This is a graph showing the low temperature water and sulfur resistance of the CuFe-SAPO-34-1 molecular sieve obtained in Example 1;

[0032] Figure 5 This is a SEM image of the CuFe-SAPO-34-2 molecular sieve obtained in Example 2;

[0033] Figure 6 This is a SEM image of the CuFe-SAPO-34-3 molecular sieve obtained in Example 3;

[0034] Figure 7 This is a SEM image of the CuFe-SAPO-34-4 molecular sieve obtained in Example 4;

[0035] Figure 8 This is a SEM image of the Cu-SAPO-34 molecular sieve obtained in Example 5;

[0036] Fig. 9 The denitration performance diagram of the fresh sample and the low-temperature hydrothermal aged sample of Cu-SAPO-34 molecular sieve obtained in Example 5;

[0037] Fig.10 This is a graph showing the low-temperature water and sulfur resistance of the Cu-SAPO-34 molecular sieve obtained in Example 5. DETAILED DESCRIPTION

[0038] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is described in detail below with reference to the accompanying drawings, but it should not be construed as limiting the scope of implementation of the present invention.

[0039] Example 1

[0040] Preparation of CuFe-SAPO-34 molecular sieve

[0041] Selection of minerals: The kaolin used is a commercial product, and its main components are: SiO2 content is 53.1wt%, Al2O3 content is 44.1wt%, and Fe2O3 content is 3.5wt%. The natural copper ore used is commercially available chlorotacrocite, and its main component is: Cu content is 59.4wt%.

[0042] Activation of minerals: kaolin and chlorotacomite in a mass ratio of 5:1 were placed in a high-speed crusher, crushed at 5000 r / min for 60 min, and then calcined in a muffle furnace at 800°C for 6 h; the calcined mineral mixture was mixed with a 14 mol / L phosphoric acid solution in a mass ratio of 1:2, and reacted at 30°C for 24 h.

[0043] Molecular sieve preparation: fully activated minerals were mixed with phosphoric acid and pseudo-boehmite in a molar ratio of 1Al2O3 / 0.8SiO2 / 1P2O5 / 0.12Cu, dried in an oven at 100°C for 6 hours, and then ground into dry gel powder. The dry gel powder was placed in a built-in weighing bottle of a reactor, and deionized water and triethylamine were added to the bottom of the reactor. The molar ratio of deionized water, triethylamine and Al2O3 in the dry gel was 1Al2O3 / 3TEA / 50H2O. After the reactor was crystallized in an oven at 180°C for 72 hours, the product was centrifuged, the solid product was washed with deionized water to pH=7, and then dried in an oven at 80°C overnight. After being calcined in a muffle furnace at 600°C (heating rate 2°C / min) for 2 hours, the CuFe-SAPO-34 molecular sieve was obtained and named CuFe-SAPO-34-1.

[0044] XRD spectrum of CuFe-SAPO-34-1 sample ( Figure 1 ) proves that it is a CHA topological structure, and no CuO and Fe2O3 diffraction peaks appear, indicating that Cu and Fe species are highly dispersed in the molecular sieve; SEM image ( Figure 2 ) shows that its morphology is a cube formed by self-assembly of nanosheets, the thickness of the sheet is 2nm, and the grain size is 3-4μm. According to XRF, the Cu and Fe contents of the sample are 3.7% and 1% respectively.

[0045] Activity evaluation: CuFe-SAPO-34-1 catalyst was pressed into tablets and sieved into 20-40 mesh particles. -1 The denitration performance test was carried out at 100 °C space velocity; the catalyst was subjected to low-temperature hydrothermal aging at 70 °C; and the low-temperature water and sulfur resistance test was carried out under the conditions of 200 ppm SO2 and 10% H2O. The denitration performance results of the fresh sample and the low-temperature hydrothermal aging sample are shown in Table 1 and Figure 3 As shown, the low temperature water and sulfur resistance results are as follows Figure 4 shown.

[0046] Table 1 NO of fresh CuFe-SAPO-34-1 samples and low-temperature hydrothermal aged samples x Conversion rate

[0047]

[0048] From Table 1, Figure 3 , Figure 4 It can be seen that the catalyst has a NO x The conversion rate can reach more than 90%, indicating that it has excellent NH3-SCR catalytic activity and a wide active temperature window; after low-temperature hydrothermal aging treatment, the catalyst has a x Although the conversion rate has decreased, it still maintains a wide active temperature window (200-475°C). At 200°C, 200 ppm SO2 and 10% H2O are introduced and reacted for 6 hours. x The removal rate can still be maintained above 90%, indicating that the catalyst has excellent low-temperature water and sulfur resistance.

[0049] Example 2

[0050] Preparation of CuFe-SAPO-34 molecular sieve

[0051] Selection of minerals: The kaolin used is a commercial product, and its main components are: SiO2 content is 53.1wt%, Al2O3 content is 44.1wt%, and Fe2O3 content is 3.5wt%. The natural copper ore used is commercially available chalcocite, and its main component is: Cu content is 79.9wt%.

[0052] Activation of minerals: kaolin and chalcocite in a mass ratio of 1:1 were placed in a high-speed crusher, crushed at 15000r / min for 40min, and then calcined in a 300°C muffle furnace for 14h; the calcined mineral mixture was mixed with a 5mol / L phosphoric acid solution in a mass ratio of 1:11, and reacted at 40°C for 16h.

[0053] Molecular sieve preparation: fully activated minerals were mixed with phosphoric acid and pseudo-boehmite in a molar ratio of 1Al2O3 / 0.2SiO2 / 0.7P2O5 / 0.06Cu, dried in an oven at 80°C for 12 hours, and then ground into dry gel powder. The dry gel powder was placed in a built-in weighing bottle of a reactor, and deionized water and n-butylamine were added to the bottom of the reactor. The molar ratio of deionized water, n-butylamine and Al2O3 in the dry gel was 1Al2O3 / 1.8BA / 30H2O. After the reactor was crystallized in an oven at 200°C for 48 hours, the product was centrifuged, the solid product was washed with deionized water to pH=7, and then dried in an oven at 80°C overnight. After being calcined in a muffle furnace at 400°C (heating rate 2°C / min) for 8 hours, the CuFe-SAPO-34 molecular sieve was obtained and named CuFe-SAPO-34-2.

[0054] SEM image of CuFe-SAPO-34-2 sample ( Figure 5 ) shows that its morphology is a cube formed by self-assembly of nanosheets, the thickness of the sheet is 90nm, and the grain size is 20-21μm. According to XRF, the Cu and Fe contents of the sample are 0.5% and 3.1% respectively.

[0055] Activity evaluation: CuFe-SAPO-34-2 catalyst was pressed into tablets and sieved into 20-40 mesh particles. -1 The denitrification performance test was carried out at an air velocity of 1.5 0.1 g / cm2, and the results are shown in Table 2.

[0056] Table 2 NO of CuFe-SAPO-34-2 sample x Conversion rate

[0057]

[0058] As shown in Table 2, the NO x The conversion rate can reach over 90%.

[0059] Example 3

[0060] Preparation of CuFe-SAPO-34 molecular sieve

[0061] Selection of minerals: The kaolin used is a commercial product, and its main components are: SiO2 content is 53.1wt%, Al2O3 content is 44.1wt%, and Fe2O3 content is 3.5wt%. The natural copper ore used is commercially available hydrochloric acid, and its main component is: Cu content is 56.1wt%.

[0062] Activation of minerals: kaolin and hydrochloric acid in a mass ratio of 3:1 are placed in a high-speed crusher, crushed at 25000r / min for 20min, and then calcined in a muffle furnace at 600℃ for 10h; the calcined mineral mixture is mixed with a 10mol / L phosphoric acid solution in a mass ratio of 1:3, and reacted at 70℃ for 8h.

[0063] Molecular sieve preparation: fully activated minerals are mixed with phosphoric acid and aluminum isopropoxide in a molar ratio of 1Al2O3 / 0.7SiO2 / 1.1P2O5 / 0.23Cu, dried in a 50°C oven for 24 hours, and then ground into dry gel powder. The dry gel powder is placed in a built-in weighing bottle of a reactor, and deionized water and diisopropanolamine are added to the bottom of the reactor. The molar ratio of deionized water, diisopropanolamine and Al2O3 in the dry gel is 1Al2O3 / 3.4DIPA / 100H2O. After the reactor is crystallized in a 220°C oven for 24 hours, the product is centrifuged, the solid product is washed with deionized water to pH=7, and then dried in an 80°C oven overnight. After being calcined in a muffle furnace at 700°C (heating rate 2°C / min) for 6 hours, the CuFe-SAPO-34 molecular sieve is obtained and named CuFe-SAPO-34-3.

[0064] SEM image of CuFe-SAPO-34-3 sample ( Figure 6 ) shows that its morphology is a cube formed by self-assembly of nanosheets, the thickness of the sheet is 30nm, and the size of the cube grain is 12-14μm. According to XRF, the Cu and Fe contents of the sample are 5.8% and 4.3% respectively.

[0065] Activity evaluation: CuFe-SAPO-34-3 catalyst was pressed into tablets and sieved into 20-40 mesh particles. -1 The denitrification performance test was carried out at an air velocity of 1.5 0.1 g / cm2, and the results are shown in Table 3.

[0066] Table 3 NO of CuFe-SAPO-34-3 sample x Conversion rate

[0067]

[0068] As shown in Table 3, the NO x The conversion rate can reach over 90%.

[0069] Example 4

[0070] Preparation of CuFe-SAPO-34 molecular sieve

[0071] Selection of minerals: The kaolin used is a commercial product, and its main components are: SiO2 content is 53.1wt%, Al2O3 content is 44.1wt%, and Fe2O3 content is 3.5wt%. The natural copper ore used is commercially available chalcocite, and its main component is: Cu content is 79.7wt%.

[0072] Activation of minerals: kaolin and chalcocite with a mass ratio of 2:1 were placed in a high-speed crusher, crushed at 40,000 r / min for 5 minutes, and then calcined in a muffle furnace at 1000°C for 2 hours; the calcined mineral mixture was mixed with a phosphoric acid solution with a concentration of 8 mol / L at a mass ratio of 1:5, and reacted at 100°C for 1 hour.

[0073] Molecular sieve preparation: The calcined mineral complex was mixed with orthophosphoric acid and sodium aluminate in a molar ratio of 1Al2O3 / 0.6SiO2 / 1.2P2O5 / 0.36Cu, dried in an oven at 30°C for 48 hours and ground into powder. The dry gel powder was placed in a built-in weighing bottle of a reactor, and deionized water and N,N-diisopropylethylamine were added to the bottom of the reactor. The molar ratio of deionized water, N,N-diisopropylethylamine to Al2O3 in the dry gel was 1Al2O3 / 2.6DIPEA / 70H2O. After crystallization in an oven at 170°C for 96 hours, the product was centrifuged, the solid product was washed with deionized water to pH=7, and then dried in an oven at 80°C overnight. After calcination in a muffle furnace at 800°C (heating rate 2°C / min) for 4 hours, the CuFe-SAPO-34 molecular sieve was obtained and named CuFe-SAPO-34-4.

[0074] SEM image of CuFe-SAPO-34-4 sample ( Figure 7 ) shows that its morphology is a sphere formed by self-assembly of nanosheets, the thickness of the sheet is 150nm, and the cubic grain size is 48-50μm. According to XRF, the Cu and Fe contents of the sample are 9% and 2.3% respectively.

[0075] Activity evaluation: CuFe-SAPO-34-4 catalyst was pressed into tablets and sieved into 20-40 mesh particles. -1 The denitrification performance test was carried out at an air velocity of 1.5 0.2 m / s and the results are shown in Table 4.

[0076] Table 4 CuFe-SAPO-34-4 sample NO x Conversion rate

[0077]

[0078] As shown in Table 4, the NO x The conversion rate can reach over 90%.

[0079] Example 5 (Comparative Example)

[0080] Preparation of Cu-SAPO-34 molecular sieve

[0081] This comparative example adopts the same feeding sequence and initial gel composition as Example 1, only using silica sol with a content of 30wt% SiO2 instead of kaolin as the silicon source to synthesize Cu-SAPO-34 molecular sieve. The specific steps are as follows:

[0082] Selection of minerals: The natural copper ore used is commercially available chlorotacrocite, the main component of which is: Cu content is 79.9wt%.

[0083] Activation of minerals: Place the chlorotacromine in a high-speed crusher, crush it at 5000r / min for 60min, and then place it in a muffle furnace at 800℃ for calcination for 6h; mix the calcined mineral with a 14mol / L phosphoric acid solution in a mass ratio of 1:2, and react at 30℃ for 24h.

[0084] Molecular sieve preparation: fully activated minerals were mixed with phosphoric acid, pseudo-boehmite and silica sol in a molar ratio of 1Al2O3 / 0.8SiO2 / 1P2O5 / 0.12Cu, dried in an oven at 100°C for 6 hours and ground into dry gel powder, which was placed in a built-in weighing bottle of a reactor, and deionized water and triethylamine were added to the bottom of the reactor. The molar ratio of deionized water, triethylamine and Al2O3 in the dry gel was 1Al2O3 / 3TEA / 50H2O. After the reactor was crystallized in an oven at 180°C for 72 hours, the product was centrifuged, the solid product was washed with deionized water to pH=7, and then dried in an oven at 80°C overnight, and calcined in a muffle furnace at 600°C (heating rate 2°C / min) for 2 hours to obtain Cu-SAPO-34 molecular sieve.

[0085] SEM image of Cu-SAPO-34 sample ( Figure 8 ) shows that its morphology is a regular cubic structure, and the grain size is 2-3 μm. According to XRF, it is determined that the sample has the same Cu content as Example 1 (3.7%).

[0086] The Cu-SAPO-34 catalyst was pressed into tablets and sieved into 20-40 mesh particles for denitration performance and low-temperature water resistance test. The denitration performance results of the fresh sample and the low-temperature hydrothermal aging sample are shown in Table 5 and Fig. 9 The results of low temperature water and sulfur resistance are shown in Fig.10 shown.

[0087] Table 5 NO of fresh Cu-SAPO-34 samples and low-temperature hydrothermal aged samples x Conversion rate

[0088]

[0089] From Table 5, Fig. 9 , Fig.10 It can be seen that the fresh catalyst has a NO x The conversion rate can reach more than 90%, but after low-temperature hydrothermal aging treatment, the NO x The conversion rate dropped significantly over the entire temperature range. x The conversion rate was lower than 90%. At 200℃, 200ppm SO2 and 10% H2O were introduced and the NO x The conversion rate was only 42% and the catalyst was almost completely deactivated.

[0090] From the comparison between Example 1 and Example 5, it can be seen that although the fresh Cu-SAPO-34 catalyst has good NH3-SCR catalytic activity, it has the problem of poor low-temperature water and sulfur resistance. The CuFe-SAPO-34 molecular sieve nanosheet assembly prepared with iron-rich natural mineral kaolin as all silicon and iron sources shows better NH3-SCR catalytic activity and low-temperature water and sulfur resistance. The method of the present invention not only has the advantages of simple process and easy operation, but also has good economic and environmental benefits.

[0091] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a CuFe-SAPO-34 molecular sieve nanosheet assembly, characterized in that: The following steps are involved: (1) placing kaolin and copper ore in a high-speed pulverizer at a mass ratio of 1 to 5:1, and fully pulverizing and mixing them to obtain a mineral mixture; (2) placing the mineral mixture in a muffle furnace and calcining it at 300-1000 °C for 1-14 h; (3) mixing the calcined mineral mixture with 5-14 mol / L phosphoric acid in a mass ratio of 1:2-11 and reacting them fully at a reaction temperature of 30-100 °C for a reaction time of 1-24 h to obtain an activated mineral mixture; (4) mixing the activated mineral mixture with a supplemental aluminum source and phosphoric acid, stirring thoroughly, and then drying to obtain a xerogel; The amounts of the activated mineral mixture, supplementary aluminum source, and phosphoric acid meet the following conditions: the molar ratio of P2O5 / Al2O3 is 0.7-1.2, the molar ratio of SiO2 / Al2O3 is 0.2-0.8, and the molar ratio of Cu / Al2O3 is 0.06-0.36; (5) The dry gel is placed in a built-in weighing bottle of a reactor, and water and a microporous template are added to the bottom of the reactor. The molar ratio of water to Al2O3 in the dry gel is 30-100, and the molar ratio of the microporous template to Al2O3 in the dry gel is 1.8-3.

4. The reactor is sealed and transferred to an oven for crystallization. The crystallization temperature is 170-220°C, and the crystallization time is 24-96 h. After the crystallization is completed, the product is cooled, centrifuged, dried, and calcined at 400-800°C for 2-8 h to obtain a CuFe-SAPO-34 molecular sieve nanosheet assembly. The thickness of the nanosheet is 2-90 nm. The copper loading of the CuFe-SAPO-34 molecular sieve nanosheet assembly is 0.5-9 wt%, and the iron loading is 0.5-4 wt%.

2. The method for preparing a CuFe-SAPO-34 molecular sieve nanosheet assembly according to claim 1, characterized in that: The sum of the contents of silicon dioxide and aluminum oxide in the kaolin in step (1) is not less than 85 wt%, and the content of iron oxide is not less than 3 wt%; the copper ore is one or a mixture of chalcocite, cuprite, chalcopyrite, hydrochalcopyrite and chalcopyrite; the rotation speed of the high-speed pulverizer is 5000-40000 r / min, and the pulverization time is 5-60 min.

3. The method for preparing a CuFe-SAPO-34 molecular sieve nanosheet assembly according to claim 1, characterized in that: In step (4), the supplementary aluminum source is one or a mixture of pseudo-boehmite, aluminum isopropoxide, sodium aluminate, the drying temperature is 30-100°C, and the drying time is 6-48 hours.

4. The method for preparing a CuFe-SAPO-34 molecular sieve nanosheet assembly according to claim 1, characterized in that: The microporous template agent in step (5) is one or a mixture of triethylamine, tetraethylammonium hydroxide, diisopropanolamine, n-butylamine, tetraethylenepentamine, and N,N-diisopropylethylamine.

5. The CuFe-SAPO-34 molecular sieve nanosheet assembly obtained according to the preparation method according to any one of claims 1 to 4.

6. The CuFe-SAPO-34 molecular sieve nanosheet assembly as claimed in claim 5 is in NO x Application in selective catalytic reduction reactions.

Citation Information

Patent Citations

  • FeZSM-5 molecular sieve and synthetic method thereof

    CN105016355A

  • In-situ synthesis method and applications of CuFe-SAPO-34 catalyst

    CN107126973A

  • Preparation method and application of mesoporous Fe-Cu-SSZ-13 molecular sieve

    CN109382137A